Narratives of Wounded Knee - Krehbiel, Beth Ann (Kansas State University, 2016)
Research suggests that Native Americans, Chicanos, and African Americans are groups underrepresented in the North American memorial landscape. The fluid nature of a group and individual’s identity (and the memory that shapes it) contributes to the underrepresentation in commemoration and memorials. As communities and the associated identities continue to blend and overlap moments of positive cultural exchange can take place, but at times the outcomes are in the realm of contention and conflict. The collaborative nature of landscape architecture together with the profession’s ability to understand and interpret complex systems and narratives can fully engage and bring form to the morally imaginative, creative act of peacebuilding. The concept of shifting and variant meaning led to this study that considered the question- How might memorials be designed as reconciliatory agents in cultural landscapes with conflicting histories? This study engaged the concept of memory and identity with Oglala Lakota, on the Pine Ridge Reservation, regarding the tragedy of Wounded Knee, through adapted ethnographic approaches in interviewing, site visits, extensive literature review, mapping and design inquiry. The design inquiry responds to social, economic, and ecological narratives to inform the design of the reconciliatory-minded memorial. The initial premise of the project was situated in the understanding that events with contested meaning are difficult to memorialize because there are so many differing voices; irreconcilable in the built form. While that is true in some contexts, initial findings suggests these groups are underrepresented because it is difficult to memorialize that which is a contemporary social justice or inter-demographic issue. In light of this and further research, the author believes that memorials seeking to honor demographics or events that directly affect contemporary groups might be contextually more appropriate, and act as mediators, if they focus forward rather than solely and solemnly reflect the past. Conceptual sketches conclude this study, offering possibilities for design expression, which might be realized with community participation.
Keywords: Landscape Architecture; Memorial Design; Conflict Resolution; Narrative; Native American; Identity